A modular self-adjuvanting cancer vaccine combined with an oncolytic vaccine induces potent antitumor immunity - Krishna Das; Elodie Belnoue; Matteo Rossi; Tamara Hofer; Sarah Danklmaier; Tobias Nolden; Liesa-Marie Schreiber; Katharina Angerer; Janine Kimpel; Sandra Hoegler; Bart Spiesschaert; Lukas Kenner; et al. (Nature Communications, 2021)
Successful cancer immune therapy correlates with a T cell-inflamed tumour microenvironment. Authors show here that co-administration of a self-adjuvanting protein vaccine and an antigen-expressing oncolytic virus in an optimised regimen strongly enhances T cell immunogenicity and may turn non-inflamed tumours proinflammatory and less resistant to checkpoint blockade therapy.